DIRECTIONS FOR IMPROVING LIABILITY ACCOUNTING (IFRS) - Jasur Bosimovich Mukumov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In this article, the problematic areas of application of international standards of financial reporting and auditing in our country are defined in normative legal documents and the tasks of their elimination are indicated. In addition, these regulatory legal documents set the tasks of training teaching staff and practitioners working in the field of accounting and auditing based on the requirements of international standards and regularly improving their qualifications.